Application of artificial intelligence in mobile communication:challenge and practice - Yusun FU; Genke YANG (Tongxin xuebao)
The research and application progress in mobile communication,and points out its obstacle for improving the performance of mobile communication system were summarized.A new approach for reducing the gap between the practical and the ideal network performance was put forward creatively,which included the artificial intelligence reconstruction for performance outer loop part,the traditional adaptation or optimization for performance inner loop part,and the optimal cooperation between the two parts.The effectiveness of this approach was proved by the several successful applications.Finally,it pointed out that in order to meet the severe demands of mobile communication system for the “stable” “accurate” and “fast” artificial intelligence solution,and make the mobile network automatic,intelligent and wise,in addition to the excellent performance of the artificial intelligence reconstruction scheme itself,there must also be a feedback closed-loop system architecture based on the big data analysis and analog system,which is the key path to achieve this target.